Beyond the City : the Rural Contribution to Development. - De Ferranti, David M. (World Bank Latin American and Caribbean studies., 2005)
"Beyond the City: The Rural Contribution to Development, the World Bank's major annual research study on Latin America and the Caribbean, evaluates the effects of the rural economy on growth, poverty, and the environment, both in the rural space and in the national and regional economy. Prepared by a team of researchers led by Guillermo Perry, the Bank's chief economist for the region, the report brings together new theoretical and empirical treatments of the links between rural and national development. Combined with existing literature, these findings show that the importance of the rural sector has been underestimated and help to identify appropriate public policies that can enhance the sector's contribution to overall national development."--Jacket